Fresno County Economic Opportunities Commission 20 Year Anniversary Dinner; Julian Bond Keynote Speaker - Watkins, Howard::::::::: (1985)
Fresno County Economic Opportunities Commission Executive Director Joe Williams presenting an award to a retiring Board member Bright flower arrangement in front of lectern